2021
DOI: 10.1371/journal.pone.0250872
|View full text |Cite
|
Sign up to set email alerts
|

Risk communication during COVID-19: A descriptive study on familiarity with, adherence to and trust in the WHO preventive measures

Abstract: Background Risk communication is a key component of public health interventions during an outbreak. As the coronavirus pandemic unfolded in late 2019, the World Health Organization (WHO) was at the forefront in the development of risk communication strategies. The WHO introduced a range of activities with the purpose of enabling the public to avail verified and timely information on COVID-19 prevention behaviors. Given the various WHO activities to protect the public health during COVID-19, it is important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 14 publications
3
36
0
4
Order By: Relevance
“…There is a complex interplay of changes in epidemiology data, media attention, pandemic control measures, risk perception, and public health behaviour (Reintjes et al., 2016). An effective risk communication in a pandemic such as COVID‐19 must include information not just about the threat itself but also about how people perceive and respond to that threat (Abrams & Greenhawt, 2020; Varghese et al., 2021). Data gathered in our study could support effective interaction among authorities, health workers, journalists, and the public to design effective risk communication that encourages appropriate behavioural change, helps manage the crisis, and protects the most important asset in a crisis: public trust (Betsch et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is a complex interplay of changes in epidemiology data, media attention, pandemic control measures, risk perception, and public health behaviour (Reintjes et al., 2016). An effective risk communication in a pandemic such as COVID‐19 must include information not just about the threat itself but also about how people perceive and respond to that threat (Abrams & Greenhawt, 2020; Varghese et al., 2021). Data gathered in our study could support effective interaction among authorities, health workers, journalists, and the public to design effective risk communication that encourages appropriate behavioural change, helps manage the crisis, and protects the most important asset in a crisis: public trust (Betsch et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[ 87 ]; [ 88 ]; [ 89 ]; [ 90 ]; [ 91 ]; [ 92 ]; [ 93 ]; [ 94 ]; [ 95 ]; [ 96 ]; [ 97 ]; [ 98 ]; [ 99 ]; [ 100 ]; [ 101 ]; [ 102 ]; [ 103 ]; [ 104 ]; [ 105 ]; [ 106 ]; [ 107 ]; [ 108 ]; [ 109 ]; [ 110 ]; [ 111 ]; [ 112 ]; [ 113 ]; [ 114 ]; [ 115 ]; [ 116 ]; [ 117 ]; [ 118 ]; [ 119 ]; [ 120 ]; [ 121 ]; [ 122 ]; [ 123 ]; [ 124 ]; [ 125 ]; [ 126 ]; [ 127 ]; [ 128 ]; [ 129 ]; [ 130 ]; [ 131 ]; [ 132 ]; [ 133 ]; [ 134 ]; [ 135 ]; [ 136 ]; [ 137 ]; [ 138 ]; [ 139 ]; [ 140 ]; [ 141 ]; [ 142 ]; [ 143 ]; [ 144 ]; [ 145 ]; [ 146 ]; [ 147 ]; [ 148 ]; [ 149 ]; [ 150 ]; [ 151 ]; [ 152 ]; [ 153 ]; [ 154 ]; [ …”
Section: Uncited Referencesunclassified
“…Our results of NPI compliance levels were quite in line with those reported in Portugal in April 2020, regarding compliance with hand washing, respiratory hygiene and physical distancing, Portugal being the country with the highest level of adherence within the seven European countries included in the previous study. 19 Nevertheless, in March and April 2020, high levels of compliance with hand washing, respiratory hygiene and physical/social distancing have been reported internationally, with quite lower levels for facemask use. 6 , 12 , 35–39 However, other studies showed considerably lower levels of compliance to NPI measures such as social distancing (North London, May 2020) 7 or physical/social distancing and hand washing (UK, April 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we highlighted that NPI associated factors can be context-specific both in time and place. 9 , 11 , 12 , 17 , 19 , 29 Several reasons might impact NPI compliance through time, such as lockdown rules 7 or relapsing behaviours, 49 but also factors associated with its compliance. 9 Thus, close and continuous monitoring of health behaviors should be done by the public health authorities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation